White‐tailed deer age ratios as herd management and predator impact measures in pennsylvania - Christopher S. Rosenberry; Andrew S. Norton; Duane R. Diefenbach; Jeannine T. Fleegle; Bret D. Wallingford (Wildlife Society Bulletin)
Abstract A review of the Pennsylvania Game Commission's (PGC) deer management program and public concern about predator impacts on deer (Odocoileus virginianus) populations compelled the PGC to investigate the role of age ratios in developing management recommendations. Age ratios, such as proportion of juveniles in the antlerless harvest, may provide an index to population productivity and predator impacts. We estimated proportion of juveniles in the antlerless harvest from hunter‐killed deer, population trends using the Pennsylvania (USA) sex–age–kill model, and reproduction from road‐killed females. Using these estimates and a simulation model, we concluded that no single age‐ratio value would serve as a reliable measure of population status. Wildlife Management Unit‐specific trends in proportion of juveniles in the antlerless harvest and population trends provided the most relevant management information. We also provide an example decision chart to guide management actions in response to declining age ratios in the harvest. Although predator management activities and juvenile survival studies are often desired by the public, our decision‐chart example indicated a number of deer management options exist before investing resources in predator management activities and juvenile survival studies. Published 2011. This article is a U.S. Government work and is in the public domain in the USA.